Програмування в обмеженнях у системі інсерційного моделювання - Летичевський, О.А.; Летичевський, О.О.; Песчаненко, В.С.; Блинов, І.О.; Кльонов, Д.М. (Інститут програмних систем НАН України, 2011)
The paper relates to practical aspects of insertion modeling. Insertion modeling system is an environment for the development of insertion machines, used to represent insertion models of distributed systems. The architecture of insertion machines and insertion modeling system IMS is presented. Insertion machine for constraint programming is specified as an example, and as a starting point of ‘verifiable programming’ project.